Poor evacuation and flood safety measure for local victims in Pagoh Muar, Johor: implementing FRC package to aid / Nur Nabila Ab Sukor - Ab Sukor, Nur Nabila Ab Sukor (2014)
Roods have been amongst the severe natural disaster that occurs in Malaysia. Malaysia, like most tropical countries, usually blame the monsoon season for the annual occurrence. However the massive developments and human activities gives bigger impacts and negative consequences to developed country. Nowadays, flood has been a serious concern because its leads to loss of lives, destruction to property, land structure and economic loss. Although we have survived from this havoc for several times within this 100 years,Government of Malaysia is still lacks an effective legal mechanism on integration of policies and mechanisms in flood management specifically on individual flood defence and proper evacuation centre. Besides that, the high potential victims are not consequently prepared, protected and equipped to deal with emergencies that they may encounter. This paper discussed the level of safety measures among the locals, their perception of safety during the flood event and to examine the weakness of current evacuation centre in Malaysia. The study also presents some recommendations for Malaysians and the Malaysian government to improve the level of flood disaster preparedness and a systematic evacuation system.